Assessment of mouse strain differences in baseline esterase activities and toxic response to sarin. (1st December 2018) - Matson, Liana M.; Lee-Stubbs, Robyn B.; Cadieux, C. Lin.; Koenig, Jeffrey A.; Ardinger, Cherish E.; Chandler, Jessica; Johnson, Erik A.; Hoard-Fruchey, Heidi M.; Shih, Tsung-Ming A.; Cerasoli, Doug M.; McDonough, John H.
Abstract: Genetics likely play a role in various responses to nerve agent (NA) exposure, as genetic background plays an important role in behavioral, neurological, and physiological responses. This study uses different mouse strains to identify if mouse strain differences in sarin exposure exist. In Experiment 1, basal levels of acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and carboxylesterase (CE) were measured in different strains of naïve mice to account for potential pharmacokinetic determinants of individual differences. In Experiment 2, median lethal dose (MLD) levels were estimated in 8 inbred mouse strains following subcutaneous (s.c.) administration of sarin. Few strain or sex differences in esterase activity levels were observed, with the exception of erythrocyte AChE activity in the C57BL/6J strain. Both sex and strain differences in toxicity were observed, with the most resistant strains being the BALB/cByJ and FVB/NJ strains and the most sensitive strain being the DBA/2J strain. These findings can be expanded to explore pathways involved in NA response, which may provide an avenue to develop therapeutics for preventing and treating the damaging effects of NA exposure.